Rethinking Participation: A Pedagogical Overview (EAAE Annual Conference Proceedings, 2023)
In recent years, the relationships between participatory processes and the disciplines involved in space production have strengthened. Architects are now becoming more involved and playing increasingly significant roles in the framework of participatory space production. The architectural education systems, however, are not yet developed enough to support this scenario.